EMBRIOLOGY OF DERMOID CYSTS WITH NEURO-ECTODERMAL CONTENT - Dimo S. Krastev; Ina Filipova (Peytchinski Publishing, 2013)
Each of the tissues that form the human body is made up of cells and intercellular substance. Tissues do not exist in isolation, but through each other metabolic relations build organs and systems of the body during ontogeny.During embryonic development tissues take certain place but sometimes they can be combined in different proportions and in different parts of the body. Thus, the mix of tissue formed as such derived from different embryonic structures serve to store a dermoid cysts.